EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTU MEDIA GAMBAR PADA MATA PELAJARAN SENI RUPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS 2 MIS MUSLIMAT NU KOTA PALANGKA RAYA - Uswatun Hasanah; Rahmad; Sri Normuliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the low student learning outcomes in fine arts subjects, especially the material on drawing decorative patterns in class 2 of MIS Muslimat NU Palangka Raya City. This occurs due to teaching methods that are still conventional and do not actively involve students. Therefore, a more creative and participatory learning approach is needed, such as Project Based Learning (PjBL) supported by drawing media using simple materials such as turmeric and detergent as dyes. The purpose of this study is to assess how effective the implementation of the Project Based Learning (PjBL) learning model assisted by the use of drawing media, in improving student learning outcomes in fine arts learning. The research method used is quantitative with a pre-experimental type that applies pretest and posttest and uses a one-group design. The number of participants in this study was 28 students, with data collected through tests, observations, and documentation. Data analysis used descriptive statistics, Shapiro-Wilk normality tests, paired t-tests, and N-Gain assessments. From the results of the study, it was found that the results of the learning implementation took place very well, where teacher performance was assessed in the very good category and student participation was categorized as good. The average student learning score increased from 43.93 in the initial test to 87.50 in the final test. The results of the t-test showed a significance level of 0.000 (p < 0.05), indicating a significant increase in learning outcomes after the treatment. Furthermore, the average N-Gain reached 0.7522 (high category) and the percentage of 75.22% indicated that the learning model used was successful in improving student learning outcomes. In other words, the Project Based Learning model using image media has proven effective and is worthy of being recommended as a learning option to improve fine arts learning outcomes in elementary schools.